How low can we go? An assessment of greenhouse gas emissions from the UK food system and the scope reduction by 2050. Report for the WWF and Food Climate Research Network - Audsley, Eric; Brander, M.; Chatterton, Julia C.; Murphy-Bokern, Donal; Webster, C.; Williams, Adrian G. (Cranfield University, 2010)
The overall aim of this study was to develop a set of scenarios that explore how greenhouse gas emissions from the UK food system may be reduced by 70% by the year 2050. The work is focused on all emissions from the supply chains and systems, not just the emissions from the UK food chain that arise in the UK. The study comprises an audit of the greenhouse gas emissions arising from the UK food economy and an examination of the scope for substantial reductions of these emissions.